2008
DOI: 10.2495/fiva080301
|View full text |Cite
|
Sign up to set email alerts
|

The resilience ability of vegetation after different fire recurrences in Provence

Abstract: Literature on relationships between wildfires and vegetation in Mediterranean areas indicates high resilience ability for most ecosystems on calcareous soils, but data are scarce for acidic soils. The resilience ability of a "fire-driven" ecosystem is expected to depend both on the characteristics of the ecosystem and on the fire recurrence.We investigated the vegetation according to fire recurrence in a site with ecological and patrimonial stakes (the Maures massif, Provence, South Eastern France), in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Indeed, the time since the last fire was more influential than the time since the previous last fire, as previously found by Schaffhauser et al (2008). However, both TSF and fire frequency had different effects on different PTs, as hypothesized (see Fig.…”
Section: Recurrent Fires Favour Plants With Disturbance-adapted Stratsupporting
confidence: 67%
See 1 more Smart Citation
“…Indeed, the time since the last fire was more influential than the time since the previous last fire, as previously found by Schaffhauser et al (2008). However, both TSF and fire frequency had different effects on different PTs, as hypothesized (see Fig.…”
Section: Recurrent Fires Favour Plants With Disturbance-adapted Stratsupporting
confidence: 67%
“…These findings indicate that a fire interval of 10-15 years is the resilience threshold for the studied communities. However, a large pool of species was common to most plots (Ouelmouhoub and Benhouhou, 2007;Schaffhauser et al, 2008), suggesting that a long fire history has played a strong selective role in these ecosystems (Bergaglio et al, 2006), and has sometimes been more influential than land use history (Arianoutsou et al, 2002;. We also found that E. arborea cover had a highly detrimental impact on functional diversity.…”
Section: Conclusion and Implications For Community Conservation And mentioning
confidence: 68%
“…). Furthermore, variation in long‐term fire frequency can also impact local assemblage composition (Schaffhauser, Curt & Tatoni ; Vila‐Cabrera, Saura‐Mas & Lloret ). One example in which these aspects of biodiversity are affected by fire is in the Cape Floristic Region (CFR; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Differential fire intensity among localities can impact dominance patterns (Bond, Smythe & Balfour 2001) and increase phylogenetic clustering (Verdu & Pausas 2007;Ojeda et al 2010). Furthermore, variation in long-term fire frequency can also impact local assemblage composition (Schaffhauser, Curt & Tatoni 2008;Vila-Cabrera, Saura-Mas & Lloret 2008). One example in which these aspects of biodiversity are affected by fire is in the Cape Floristic Region (CFR; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience can be measured by analyzing the recovery of vegetation variables such as the fraction of vegetation cover or species composition with respect to pre-disturbance situations (Halpern 1988;Wittenberg et al 2007;Schaffhauser et al 2008;Coop et al 2016). The study of post-fire resilience is a highly relevant issue in the Mediterranean Basin, since it offers an approximation of the recovery of ecosystem services that are of value to society, and whose provisioning could be threatened as a consequence of current fire regimes and global change (Puerta-Piñero et al 2012;Seidl et al 2016).…”
Section: Introductionmentioning
confidence: 99%